The Effect of Work-Life Integration on Employee Performance With Work Environment As A Moderating Variable: Penelitian - Tresna Kusumawati; Sumarno; Cattleya Rejito; Gilang Pranajasakti; Hertya Andriani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the effect of work-life integration on employee performance, with the work environment operating as a moderating variable within modern organizational settings. In an era dominated by rapid technological advancement and flexible working arrangements, traditional boundaries between professional obligations and personal life have blurred significantly, necessitating a shift from work-life balance to work-life integration. Using a quantitative approach based on Structural Equation Modeling (SEM), this paper develops a conceptual framework grounded in Social Exchange Theory and Job Demands-Resources (JD-R) Theory. The main objective is to clarify whether combining personal and professional responsibilities enhances employee productivity and whether physical and psychological work environments strengthen or weaken this relationship. The findings aim to provide strategic insights for human resource management practitioners on structuring supportive workplace environments while implementing flexible work models